Labor and delivery care : a practical guide - Cohen, Wayne R.; Friedman, Emanuel A., 1926- (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2011)
"Labor and Delivery: The hands-on guide provides practical and timely information to help guide the clinical care of women during pregnancy. An expert team of authors present the framework to integrate information obtained from hands-on evaluation of laboring women into logical matrix for decision-making and risk avoidance. By not focusing solely on explanations of the readings and usage of technology such as ultrasound and fetal monitoring, this experience-based guide to labor care concentrates on traditional skills of observation and careful physical examinations to help obstetricians care for women during labor while improving her experience of birth"--Provided by publisher.
Cover; Contents; Dedication; Title; Copyright; Preface; How to Use This Book; Chapter 1: Communicating Effectively With Your Patient; Special aspects of parturition; Communication skills; Continuity of care; Ethics and maternal-fetal conflict; Violence; Boundaries; Does gender matter?; Goals; Further Reading; Chapter 2: Examining Your Patient; General principles; General examination; Abdominal examination; The pelvic examination; Documentation; Further Reading; Chapter 3: Normal Labor and Delivery; Terminology; Uterine contractility; Clinical course of labor; Graphic analysis of labor.
Includes bibliographical references and index.
Print version record.
Keywords: Labor (Obstetrics); Delivery (Obstetrics); Childbirth; Labor, Obstetric; Birth Injuries -- prevention & control; Delivery, Obstetric -- methods; Obstetric Labor Complications -- prevention & control; MEDICAL -- Gynecology & Obstetrics; Childbirth; Delivery (Obstetrics); Labor (Obstetrics); Electronic books; Electronic books